Evidence for intermediate S-states as initial phase in the process of oxygen-evolving complex oxidation - Jablonsky, Jiri; Lazar, Dusan (Biophysical journal, 2008)
We have analyzed flash-induced period-four damped oscillation of oxygen evolution and chlorophyll fluorescence with the aid of a kinetic model of photosystem II. We have shown that, for simulation of the period-four oscillatory behavior of oxygen evolution, it is essential to consider the so-called intermediate S-state as an initial phase of each of the S(n)-S(n+1), (n = 0, 1, 2, 3) transitions. The intermediate S-states are defined as [S(n)Y(Z)(ox)]-states (n = 0, 1, 2, 3) and are formed with rate constant k(iSn) approximately 1.5 x 10(6) s(-1), which was determined from comparison of theoretical predictions with experimental data. The assumed intermediate S-states shift the equilibrium in reaction P680(+)Y(Z)<-->P680Y(Z)(ox) more to the right and we suggest that kinetics of the intermediate S-states reflects a relaxation process associated with changes of the redox equilibrium in the above reaction. The oxygen oscillation is simulated without the miss and double-hit parameters, if the intermediate S-states, which are not the source of the misses or the double-hits, are included in the simulation. Furthermore, we have shown that the intermediate S-states, together with S(2)Q(A)(-) charge recombination, are prerequisites for the simulation of the period-four oscillatory behavior of the chlorophyll fluorescence.
Keywords: chemické modely; Computer Simulation; Chlorophyll; Models, Molecular; Oxidation-Reduction; oxidace-redukce; Photosystem II Protein Complex; fotosystém II (proteinový komplex); Oxygen; kyslík; Oscillometry; Phase Transition; počítačová simulace; chlorofyl; Models, Chemical; oscilometrie; molekulární modely; změna skupenství